The Concept of Modern Journey in Mark Twain’s The Adventures of Huckleberry Finn - Inst. Salman Hayder Jasim; Inst. Adnan Taher Rahmah (Journal of College of Education, 2024)
This study aims at exploring and presenting the significance of the journey in modern American fiction. It examines the concept of journey in literature, which has a long history since the beginning of human wanderings. It focuses on the adventures of a traveller from one place to another whether by sea or by land. Travel writers use such a theme to satirize the defects of their societies as well as the cruelty of human nature. The study shows that the concept of journey began as an impersonal theme which concentrated on the environment only rather than the traveller’s individuality. Gradually, it has changed to be personal by focusing on the traveller’s individuality. The change from impersonal impressions to personal ones has flourished in literature, particularly in modern American fiction, because the Americans themselves search for their identities, history, and heritage throughout their journeys. The present study focuses on Mark Twain (1835-1910), and his novel The Adventures of Huckleberry Finn (1885), which stands for the journey from slavery into freedom. The discussion of the novel raises questions about the significance and meaning of the concept of journey in modern American fiction.